A conflict perpetuated : China policy during the Kennedy years - Kochavi, Noam, 1961- (International history., 2002)
The first comprehensive account of China policy during the Kennedy years, this study profiles John F. Kennedy as a man whose inner struggles and disparate characteristics made for an unpredictable foreign policy. While he was often a hostage to the Cold War, to constrictive perceptions of the domestic climate, and to the image of a predatory China, Kennedy recognized Washington's finite capacity to shape events on the China Mainland. With the possible exception of a preventive strike against China's nuclear installations, he was also reluctant to run the risk of a military confrontation with Beijing. On the eve of his assassination, Kennedy may have even contemplated a China policy departure during his second term.